Interference of Morning Glory in Soybean Yield - PICCININI,F. (2018)
ABSTRACT: Weed control using herbicides with the same mechanism of action can encourage the emergence of resistant biotypes or tolerant plants. An example of this is the occurrence of morning-glory (Ipomoea sp.) in soybean crops in southern Brazil. In this sense, the aim of this study was to quantify the losses arising from two species of morning-glory weeding coexisting with soybean crop. A field study was conducted in the 2013/2014 season. The experimental design was a randomized block with four replications, with treatments being distributed in a factorial arrangement (2x2x5), which assessed the effect of competition on two soybean cultivars (TEC6029 and TEC7849) of morning-glory species (I. triloba and I. purpurea) in different population (0, 4, 8, 16 and 32 plants m-2). The interaction of soybean with different densities of morning-glory affects yield components. The first eight morning glory plants have a more intense competition, reducing productivity by 45% and 27% for TEC6029 and TEC7849 cultivars, respectively.